Pharmacovigilance - Kothari, Charmy S.; Shah, Manan; Manthan Patel, Rajvi (IntechOpen, 2019)
The book "Pharmacovigilance" describes the pathway to understand that pharmacovigilance plays a specialized and pivotal role in ensuring ongoing safety of medicinal products. Written in plain English, the book is concise, jargon-free, and facilitates an understanding of fundamentals of pharmacovigilance and explores regulatory aspects involved in pharmacovigilance.